Stress Monitoring for Anchor Rods System in Subway Tunnel Using FBG Technology - Xiaolin Weng; Haohao Ma; Jun Wang (Advances in Materials Science and Engineering)
This paper presents a model test, used on the tunnels on Xi’an Metro Line 2, as the prototype for evaluating the reinforcing effect of the anchor rod in tunnel construction in loess areas. An independently designed fiber Bragg grating (FBG) sensor was used to monitor the seven strain conditions of the rock bolts during the construction. The result shows that the axial stress of the rock bolt changes after the excavation and increases steadily with the growing pressure in the wall rock. Results additionally show that the anchor rods at the tunnel vault are subjected to a compressive stress that remains relatively constant after the primary and the secondary lining, while those at the spandrel and the corner of the tunnel are subjected to increased tensile stress. This paper demonstrates the feasibility and the superiority of FBG technology for tunnel model tests.